Systematic Review of the Effect of a Zero-Markup Policy for Essential Drugs on Healthcare Costs and Utilization in China, 2015–2021 - Liu, Wen-Yi; Hsu, Chia-Hsien; Liu, Ting-Jun; Chen, Pei-En; Zheng, Boyuan; Chien, Ching-Wen; Tung, Tao-Hsin (Frontiers in Medicine, 2021)
Objective. This systematic review aimed to discuss the effects of a zero-markup policy for essential drugs on healthcare costs and utilization in China in the years 2015–2021. Methods. We searched the PubMed, Embase, Scopus, and CINAHL databases for all associated studies carried out from 1 January 2015 to 31 May 2021 without any limitations regarding the language the papers were written in. To prevent selection bias, grey documents were tackled by other means. The methodological approaches were assessed by applying the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and the Newcastle Ottawa Scale Collaboration tool. Results. Forty studies were selected at first, fifteen studies of which met the inclusion criterion. Most of the studies showed a considerable decrease in both the overall cost and the spending on drugs for each patient visit. The medical services for the outpatients and inpatients revealed an annual growth in the number of patients visiting. However, no significant evidence was indicated about facility revenue, drug revenue, gov subsidy. Conclusions. In conclusion, although the government could implement a zero-markup policy and potentially generate decrease medical cost and drug cost, the available data do not support the link between a zero-markup policy for decreased healthcare utilization, and other (facility revenue, drug revenue, and gov subsidy). Further follow-up studies that contain information on medical institutions across a broad range of districts would make our knowledge of the possible overall impact of zero-markup policy for essential drugs on patients, facility, and gov. more reliable.